Direct Transcription of Two‐Dimensional Colloidal Crystal Arrays into Three‐Dimensional Photonic Crystals. (8th October 2012) - Vlad, Alexandru; Frölich, Andreas; Zebrowski, Thomas; Dutu, Constantin Augustin; Busch, Kurt; Melinte, Sorin; Wegener, Martin; Huynen, Isabelle
Abstract A simple protocol for the fabrication of three‐dimensional (3D) photonic crystals in silicon is presented. Surface structuring by nanosphere lithography is merged with a novel silicon etching method to fabricate ordered 3D architectures. The SPRIE method, sequential passivation reactive ion etching, is a one‐step processing protocol relying on sequential passivation and reactive ion etching reactions using C4F8 and SF6 plasma chemistries. The diffusion of fresh reactants and etch product species inside the etched channels is found to play an important role affecting the structural uniformity of the designed structures and the etch rate drift is corrected by adjusting the reaction times. High quality photonic crystals are thus obtained by adding the third dimension to the two‐dimensional (2D) colloidal crystal assemblies through SPRIE. Careful adjustments of both mask design and lateral etch extent balance allow the implementation of even more complex functionalities including photonic crystal slabs and precise defect engineering. 3D photonic crystal lattices exhibiting optical stop‐bands in the infrared spectral region are demonstrated, proving the potential of SPRIE for fast, simple, and large‐scale fabrication of photonic structures.